2014
DOI: 10.1530/eje-14-0381
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum cystatin C and diabetic peripheral neuropathy: a cross-sectional study of a Chinese type 2 diabetic population

Abstract: Objective: Serum cystatin C (CysC) is a sensitive marker of kidney function and recent studies have shown that CysC plays a critical role in degenerative diseases in both the central and the peripheral nervous systems. The aim of this study was to explore the relationship between serum CysC and diabetic peripheral neuropathy (DPN) in patients with type 2 diabetes. Methods: In total, 937 type 2 diabetic patients were enrolled in this cross-sectional study. Serum CysC concentration was measured by immunoturbidim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
22
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 25 publications
6
22
0
1
Order By: Relevance
“…The levels of NSE [22], CysC [23], and TNF-a [24] are reported to be positively correlated with DPN. Many conditions and diseases (such as tumors, diabetic nephrology, and inflammatory diseases) can affect the serum levels of these markers, and may also overlap with DPN.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of NSE [22], CysC [23], and TNF-a [24] are reported to be positively correlated with DPN. Many conditions and diseases (such as tumors, diabetic nephrology, and inflammatory diseases) can affect the serum levels of these markers, and may also overlap with DPN.…”
Section: Discussionmentioning
confidence: 99%
“…Cystatin-C was shown to be significantly elevated in subjects with peripheral neuropathy. Hu, et al 2014 observed similar finding in Chinese population and inferred that serum Cystatin-C may be a biomarker for peripheral neuropathy [6]. In peripheral neural diseases, Cystatin-C could be released from neurons and affected Schwann cells into endoneurial fluid through the endoneurium.…”
Section: Discussionmentioning
confidence: 73%
“…In peripheral neural diseases, Cystatin-C could be released from neurons and affected Schwann cells into endoneurial fluid through the endoneurium. Hence, elevated serum Cystatin-C concentration may indicate diabetic peripheral nerve injury and associated demyelination [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from renal function, cystatin C recently has been found to be associated with cardiovascular events . In addition, our previous studies have demonstrated that serum cystatin C was a strong marker for lower limb ischemia and diabetic peripheral neuropathy in Chinese type 2 diabetic patients . However, so far as we know, the association of this small molecular weight protein with the therapeutic DFU outcome remains undetermined, and no ideal serum marker is available to predict the prognosis of DFU.…”
mentioning
confidence: 99%